Вивчення механізмів підвищення біосумісності різних речовин з біологічними структурами за допомогою поліетіленгліколей методом спінових зондів - Іванов, Л. В.; Картель, М. Т.; Щербак, О. В.; Кравченко, В. Г. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2019)
Hydrophobic spin-labeled carboline and a number of spin-labeled steroids dissolve well in both pure PEG and aqueous PEG solutions, demonstrating the presence of a triplet in the EPR spectrum. It was shown that the introduction of 20% aqueous solutions of PEG mol. m. from PEG-200 to PEG-40,000, the hydrophobic spin of labeled progesterone or carboline from the hydrophobic cavity of SAB is effectively displaced into the solution of bovine serum albumin (SAB) by competing with the hydrophobic cavity of SAB. Polyethylene glycols demonstrate full biocompatibility even with hydrophobic biological structures and, as biocompatibility enhancers, are universal. Analysis of the curve of the dependence of PEG microviscosity on mol. m. shows the presence of an inflection point on the curve in the area of the pier. m. 300-400, which indicates the compaction of the structure of PEG and corresponds to published data on the partial helixing of a polyethylene glycol molecule, starting with PEG-400 and above, in which the main role is played by hydrogen bonds of the PEG molecule. Methylene hydrophobic PEG residues appear inside the polyethylene glycol helix, and the polar groups providing the PEG molecules with osmotically active properties and causing dehydration of cell membranes appear outside the PEG helix. Therefore, with the growth of mol. m. PEG ability to dehydrate cells increases. Apparently, the mechanism of increasing PEG biocompatibility is the ability of PEG molecules to compact, spiralize, or expand molecules to accept the optimal conformation of the structure, providing their hydrophobic or polar groups for optimal binding on the one hand to nanoparticles and, on the other, to a bioobject. The introduction of conjugates of PEG nanoparticles into cells, which oppositely affects the microviscosity of membranes and compensates for the negative effect of nanoparticles on membranes, is the second mechanism for increasing the biocompatibility of nanoparticles. The possibility of the interaction of PEG with nanochorns with the orientation of PEG units along the cone needles (nanotubes) of nanochorns has been shown to increase the biocompatibility of nanochorns.